An Assessment of Community Health Needs Assessment (CHNA) Data Collection Related to Building Capacity for Sexual and Gender Marginalized (SGM) Individuals in Health Care Organizations - Grummel, John A.; Collins, Jaime (Journal of Management Policy and Practice, 2021)
This research examines LGBTQ+ data collection for Community Health Needs Assessments (CHNA) by Wisconsin Health care organizations as mandated by the Affordable Care Act, and whether data collection considered LGBTQ+ populations. If collected, it assesses what types of LGBTQ+ data was collected and how it was used and/or reported in the CHNA. Furthermore, a comparison by location (rural/urban) regarding whether there is a difference in likelihood that a health care organization would collect LGBTQ+ data. The results of this study indicate that data collection is collected by approximately one-quarter of Wisconsin health care organizations for the purpose of their CHNAs and there is not a significant difference by location regarding inclusion of LGBTQ+ data.